Education on Processing Used Cooking Oil Into Valuable Aromatherapy Candles as an Effort to Reduce Household Waste in Pandansari Village - Yundhiafi, Zaenab Zahro; Muaziz , Agil Abdul; Abidah, Farah; Arsy, Raihan Al; Maulana, Dimas Hisyam; Wistu, Arabila; Listiani, Nisa Ahsanu; Farinda, Firani Alisia; Nashifah, Difi Putri; Ivana, Elza; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Used cooking oil is a household waste that has the potential to pollute the environment and pose a health hazard if disposed of or reused repeatedly. The Community Service Learning (CSL) activity in Pandansari Village, Sruweng Subdistrict, Kebumen utilized used cooking oil as raw material for making aromatherapy candles. The activity was carried out in two phases: an educational session and hands-on practice in making aromatherapy candles using simple household tools, with the main ingredients being used cooking oil, stearin, dye, and essential oils. The activity was conducted at the Pandansari Village Hall together with the local community, allowing participants to build strong bonds. The results of the activity showed that the candles produced had an attractive shape, long-lasting aroma, and satisfactory burning time. In addition to providing an environmentally friendly waste management solution, this program also opened up opportunities for household businesses and increased community awareness of creative and sustainable waste management. The impact of this activity includes reducing the potential for environmental pollution.